2021
DOI: 10.3389/fnagi.2021.625690
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid and the Risk of Dementia: A Systematic Review and Meta-Analysis

Abstract: Background: This meta-analysis aimed to evaluate the relationship between serum uric acid (UA) and the risk of dementia and its subtypes.Methods: Embase, PubMed, and Web of Science were searched from inception to July 2020. Random-effect models were employed to analyze the standard mean difference (SMD) with the corresponding 95% confidence intervals (CI).Results: Twenty-three eligible studies involving 5,575 participants were identified. The overall results showed lower levels of UA in dementia relative to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 68 publications
(70 reference statements)
3
33
0
Order By: Relevance
“…There is also evidence on the relationship between low serum concentrations of UA and increased risk of dementia. A recent systematic review and meta-analysis by Zhou et al (2021) found low concentrations of UA to act as a potential risk factor for AD and PDD but not for VD. However, it has also been found evidence in the opposite direction and higher concentrations of UA have been associated with an increased likelihood of dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence on the relationship between low serum concentrations of UA and increased risk of dementia. A recent systematic review and meta-analysis by Zhou et al (2021) found low concentrations of UA to act as a potential risk factor for AD and PDD but not for VD. However, it has also been found evidence in the opposite direction and higher concentrations of UA have been associated with an increased likelihood of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…However, UA may also act as a pro-inflammatory compound and there still exists discussion on its oxidant-antioxidant properties ( Sautin and Johnson, 2008 ). UA levels have been associated with cognitive performance ( Annanmaki et al, 2008 ), MCI ( Rinaldi et al, 2003 ; Pellecchia et al, 2016 ), different types of dementia ( Rinaldi et al, 2003 ; Kim et al, 2006 ; Schlesinger and Schlesinger, 2008 ; Ruggiero et al, 2009 ; Al-Khateeb et al, 2015 ; Wen et al, 2017 ; Xu et al, 2017 ; Latourte et al, 2018 ; Serdarevic et al, 2020 ; Boccardi et al, 2021 ) and risk of dementia ( González-Aramburu et al, 2014 ; for a review see Schlesinger and Schlesinger, 2008 ; for a meta-analysis see Khan et al, 2016 ; Zhou et al, 2021 ). Other micronutrients or blood biochemistry variables that have been related to CS although studies are more scarce, are serum iron, ferritin, and transferrin ( Umur et al, 2011 ; Yavuz et al, 2012 ), total cholesterol (TC), High Density Lipoprotein Cholesterol (HDL-C), Low Density Lipoprotein Cholesterol (LDL-C) ( Van Exel et al, 2002 ; Van Vliet, 2012 ; Crichton et al, 2014 ; Lv et al, 2016 ; Ma et al, 2017 ), zinc ( Cuajungco and Fagét, 2003 ; Lam et al, 2008 ; Nuttall and Oteiza, 2014 ), Mean Corpuscular Volume (MCV) ( Gamaldo et al, 2013 ), calcium ( Schram et al, 2007 ), insulin ( Stolk et al, 1997 ), gamma-glutamyl transferase (GGT) ( Lee et al, 2020 ; Tang et al, 2021 ), alanine aminotransferase (ALT) ( Nho et al, 2019 ), and glucose ( Korol and Gold, 1998 ; Seetharaman et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, higher SUA levels have been hypothesized to play a protective role in the development of some neurological disorders such as dementia, multiple sclerosis, Alzheimer's disease and Parkinson's disease (39)(40)(41)(42). In a recent metaanalysis involving 5,575 participants, Zhou et al demonstrated a significant inverse association between SUA and Alzheimer's disease or Parkinson's disease (43). Moreover, the authors found a linear dose-response relationship between UA values and risk of dementia.…”
Section: Uric Acid As Protective Factormentioning
confidence: 99%
“…Among other fluid biomarkers, vitamin D, lipids, and neurotrophic factors have been explored in LBD and in dementia overall [109,[220][221][222][223][224][225], in addition to synaptic and cytosolic proteins, circulating mitochondrial DNA, and fatty acid binding protein 3 [109,186,226,227]. For instance, low uric acid has been shown to be possibly involved in the occurrence of LBD and cognitive decline [228,229].…”
Section: Other Biological Fluid Biomarkersmentioning
confidence: 99%